THE USE OF REWARD AND PUNISHMENT TO INCREASE YOUNG LEARNERS’ MOTIVATION IN LEARNING ENGLISH AS FOREIGN LANGUAGE ADAPTED TO INDONESIAN CONTEXT - Irawati Irawati; An Fauzia Rozani Syafei (Universitas Negeri Padang, 2016)
This paper explains about the use of reward and punishment to increase young learners’ motivation in learning English as foreign language in Indonesia. The writer discusses about procedure and advantages of reward and punishment. Reward is an appreciation given by the teacher to the students who can follow the lesson well and finishing the assignment. Meanwhile, punishment is a bad treatment that is given to the students who do not focus in learning process, do not care of their assignment, and have bad habit during the class. Reward and punishment can be given through verbal and non- verbal form (action). Kinds of reward are mimic, gesture, compliment or positive feedback, point or sticker, and present. Kinds of punishment are warning, memorizing vocabulary, decreasing students’ point, and moving students’ seat. Besides to motivate student, reward and punishment also make the students become more discipline and study harder than before.